Age-Related Downregulation of CCN2 Is Regulated by Cell Size in a YAP/TAZ-Dependent Manner in Human Dermal Fibroblasts: Impact on Dermal Aging - Zhaoping Qin; Tianyuan He; Chunfang Guo; Taihao Quan (Elsevier, 2022)
CCN2, a member of the CCN family of matricellular proteins, is a key mediator and biomarker of tissue fibrosis. We previously reported that CCN2 is significantly reduced in aged human dermis, which contributes to dermal aging through the downregulation of collagen production, the major structural protein in the skin. In this study, we investigated the underlying mechanisms of the age-related downregulation of CCN2 in human skin dermal fibroblasts. Dermal fibroblasts isolation and laser-capture microdissection‒coupled RT-PCR from human skin confirmed that age-related reduction of CCN2 expression is regulated by epigenetics. Mechanistic investigation revealed that age-related reduction of CCN2 is regulated by impaired dermal fibroblast spreading/cell size, which is a prominent feature of aged dermal fibroblasts in vivo. Gain-of-function and loss-of-function analysis confirmed that age-related downregulation of CCN2 is regulated by YAP/TAZ in response to reduced cell size. We further confirmed that restoration of dermal fibroblast size rapidly reversed the downregulation of CCN2 in a YAP/TAZ-dependent manner. Finally, we confirmed that reduced YAP/TAZ nuclear staining is accompanied by loss of CCN2 in aged human skin in vivo. Our data reveal a mechanism by which age-related reduction in fibroblast spreading/size drives YAP/TAZ-dependent downregulation of CCN2 expression, which in turn contributes to loss of collagen in aged human skin.